Plant species diversity in the ecological species groups in the Kandelat Forest Park, Guilan, North of Iran (Biodiversitas Journal of Biological Diversity, 2011)
Pourbabaei H, Haghgooy T. 2012. Plant species diversity in the ecological species groups in the Kandelat Forest Park, Guilan, North of Iran. Biodiversitas 13: 7-12. Forest vegetation indicates conditions and productivity potential of forest habitat, because it reflects the interaction of climate, soil and topography. The aim of this research was to study relationship between vegetation and topography factors. In order to do this research, type, number and percentage cover of trees, shrubs (sample plot with 1000 m2 area) and type and percentage cover of herbaceous species (sample plot with 64 m2 area) investigated and recorded. The coverage percent of species were estimated on the basis of Domin scale. Vegetation classified using Two-Way Indicator Species Analysis (TWINSPAN). The results revealed that there were 6 ecosystem units (ecological groups) in the region. The comparison of diversity indices and topographicfactors between groups were performed with ANOVA test. Results also indicated that there were significant differences between groups in terms of biodiversity indices and topographic factors. The formation of a particular group is affected by a combination of environment variables. The aspect was the most important variable of topographic factors in this study.
Keywords: ecological species groups, Guilan, Iran, Kandelat, plant species diversity, topography